Courtship and mating behaviour of manta rays Mobula alfredi and M. birostris in the Maldives. Issue 2 (21st September 2018) - Stevens, Guy M. W.; Hawkins, Julie P.; Roberts, Callum M.
Abstract : The aim of this 14 year study was to elucidate the entire courtship and mating behaviour of manta rays Mobula alfredi and M. birostris using behavioural observations, video and photographic records. From 2003 to 2016, over 11, 000 surveys were undertaken at known manta ray aggregation sites in the Maldives to record any observed manta rays reproductive activity. From 47, 591 photo‐ID sightings, 4, 247 individual M. alfredi were identified and 226 individual M. birostris from 229 photo‐ID sightings, all recorded at 22 atolls across 265 different sites. Courtship activity was observed on 206 surveys at 30 different sites. A total of 229 courtship events were recorded, with 90% ( n = 205) of them occurring at cleaning sites. The observed courtship activity was categorised into seven distinct stages which are described in detail: initiation, endurance, evasion, pre‐copulatory positioning, copulation, post‐copulatory holding and separation. Photographs provide the first scientific record of the entirety of manta rays courtship and mating. Both M. alfredi and M. birostris appear to engage in the same elaborate courtship rituals, exhibiting the same behaviours during all stages of the courtship and mating process.